ANALISIS SWOT DALAM MERUMUSKAN STRATEGI PEMASARAN UMKM UD. RISNA MEUBEL PADA MASA PANDEMI COVID-19 - Farsita, Firda; Karmeli, Elly; Sumbawati, Novi Kadewi (Fakultas Ekonomi dan Manajemen, 2023)
This study aims to formulate appropriate strategies to improve marketing performance at UD.Risna Meubel MSMEs during the Covid-19 pandemic using SWOT analysis. This study used descriptive methods to provide a systematic description of marketing strategies at UD. Risna Meubel MSMEs during the Covid-19 pandemic used SWOT analysis. The data used in this study was qualitative data in the form of information related to internal and external conditions at UD. Risna Meubel MSMEs during the Covid-19 pandemic. The researchers obtained this data directly from several informants who served as sources. The data used in this study was collected using structured interview techniques. The data that has been collected will be analyzed using SWOT analysis techniques to determine the most appropriate strategy for improving marketing performance at UD.Risna Meubel MSMEs during the Covid-19 pandemic. The results of this study showed that the position of UD. Risna Meubel MSMEs was in quadrant I. The strategy that can be implemented in this condition is to support aggressive policies (growth oriented strategy). This can be done by taking advantage of the strengths and opportunities they have to overcome the weaknesses and threats they face so that they can improve marketing at UD. Risna Meubel MSMEs. Based on the results of the SWOT analysis, four strategies can be formulated to improve marketing performance at UD. Risna Meubel MSMEs during the Covid-19 pandemic, namely SO strategy (strengths-opportunities), WO strategy (weaknesses-opportunities), ST strategy (strengths-threats) and WT strategy (weaknesses-threats).